Pengembangan Media Pembelajaran Game Edukasi Baamboozle menggunakan model Assure Pada Materi Konsep Fikih Dalam Islam Dikelas X MA Hidayatul Insan - Santidar, Ario Dwi; jasiah (JOURNAL SAINS STUDENT RESEARCH, 2025)
This research focuses on the development of an innovative educational game media, Baamboozle, for the concept of fiqh material in class X at MA Hidayatul Insan. The main objective of this study is to enhance student engagement in the learning process of fiqh, which is often perceived as difficult. Through a systematic ASSURE model approach, this research designs an educational game tailored to the characteristics of the students and the learning objectives to be achieved. The development process includes analyzing student needs, formulating specific learning objectives, selecting the interactive and engaging Baamboozle media, and developing fiqh material presented in a challenging game format. It is hoped that the implementation of the Baamboozle educational game will have a significant positive impact on student motivation and interest in learning. Students become more active, enthusiastic, and involved in the learning process. The development of this educational media contributes significantly to improving the quality of fiqh education in schools. The Baamboozle educational game can serve as an interesting and effective alternative for teachers in evaluating complex fiqh material. Additionally, this research provides recommendations for the development of other game-based educational media, particularly in the field of religious education. Thus, it is hoped that educational games can become an integral part of the learning process in the future, thereby enhancing the overall quality of education.